Superparamagnetic property and high microwave absorption performance of FeAl@(Al, Fe)2O3 nanoparticles induced by surface oxidation. Issue 24 (28th June 2015) - Liu, Tong; Pang, Yu; Kikuchi, Hiroaki; Kamada, Yasuhiro; Takahashi, Seiki
<x xml:space="preserve">Abstract</x> FeAl@(Al, Fe)2O3 nanoparticles are prepared by the hydrogen plasma-metal reaction method and passivation process. The formation of an Fe-enriched zone offers these nanoparticles superparamagnetic property and high microwave absorption performance.